Optimasi Produksi dan Mutu Benih Padi Varietas PBM UBB 1 dengan Bakteri Pelarut Fosfat dan Pupuk Fosfat: Optimasi Produksi dan Mutu Benih Padi Varietas PBM UBB 1 dengan Bakteri Pelarut Fosfat dan Pupuk Fosfat - Kartika Kartika; M. Rahmad Suhartanto; Abdul Munif; Endah Retno Palupi; Satriyas Ilyas (Universitas Bangka Belitung, 2022)
One of the problems for phosphate fertilizing in ultisol soil is Al and Fe bounding and could be overcome by phosphate solubilizing bacteria activity.This study aimed to obtain the best dose of phosphate fertilizer with phosphate solubilizing bacteria for the production of upland rice seeds of the UBB1 PBM variety (Bangka Belitung University red rice 1) and its effect on seed quality. The research was carried out at the Research and Experimental Gardens – Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, from August to December 2020. The design used was a split plot design, the main plot was phosphate solubilizing bacteria (treatment and control), and the subplots were fertilizers. phosphate (P1– quarter dose, P2– half dose, P2–three-quarter dose, P4– full dose). Seeds produced in the field were tested in the laboratory for viability and vigor. In the field, phosphate solubilizing bacteria (Burkholderia sp) can replace half the dose of phosphate fertilizer. This was indicated by the seed weight of plant-1 which did not differ between full dose + control and half dose + treatment. This fact was also identified in the viability and vigor of the seeds in laboratory testing. There was no significant difference in germination rate and vigor index between the two treatments. This finding shows that phosphate solubilizing bacteria can be applied for efficiency of phosphate fertilization and guaranteeing seed production and seed quality